Pertukaran Peran Nafkah Suami-Istri Dan Implikasinya Terhadap Hak Waris Dalam Perspektif Hukum Islam - Feninda Alaeiyka Selma Rasyid; Tuti Harwati (Pusat Studi Gender dan Anak Universitas Islam Negeri (UIN) Mataram, 2026)
Classical Islamic jurisprudence establishes financial support (nafkah) as an absolute obligation for husbands, which serves as the foundation for traditional inheritance distribution. However, contemporary Muslim family dynamics are increasingly defined by role reversals, where wives often become the primary breadwinners, creating tension between textual legal norms and the reality of substantive justice. This study aims to analyze the juridical implications of these role reversals on a wife's inheritance status by reinterpreting the principles of qiwāmah and maqāṣid al-syarī‘ah. Utilizing a normative-contextual legal research method, this study finds that shifts in economic roles necessitate a re-conceptualization of inheritance proportions—one no longer based solely on gender, but on the distribution of actual economic burdens. The urgency of this discussion lies in the need for Islamic law to remain relevant in resolving contemporary family disputes. The findings contribute theoretically to the development of Ahwal al-Syakhshiyyah and provide practical guidelines for religious courts in upholding substantive justice in family asset distribution.